(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2018)
The common eel (Ophichthus remiger) is a species of commercial value, of which, the biologicalfishing aspects as the biometric relations are poorly known. The aim of this work was to determine the morphometric characteristics of the common eel in Ecuador as the otoliths and the correlation of those with the size and weight. Size data of this species collected by the Instituto Nacional de Pesca were analyzed at the landing ports of Manta, Anconcito and Posorja, and 241 pairs of otoliths were extracted from samples at those sites. The sizes (length and width) and the weight of otoliths were compared between the left and right side of males and females and between those by analysis of variance of a factor (ANOVA) and multivariate (MANOVA). Linear regressions between sizes and weights of otoliths correlated to the total length of organisms were performed. No significant differences were found between left and right side otoliths in each sex (p> 0.05); however, differences among males and females (p <0.01) were found. The common eel presented an isometric growth between the length and width of otoliths, those were correlated to the size of the organism, the allometry correlated to weight was negative, and two groups of data were found on the latter. The otoliths are similar on both sides of each sex, that indicates the validity of the choice of one or the other in retrocalculus analysis. The differences found in the sizes of otoliths may be due to genetic or environmental conditions. The two groups of data found in the relationship between otolith’ weight and body size can be explained as individual differentiation by the degree of gonadal development.